TRANING OF MODERN ENTREPENEURS AS AN IMPORTANT FACTOR IN THE INNOVATION DEVELOPMENT OF THE FAR EAST RUSSIAN ACTORS - Konstantinovna, Pililyan Elena (PEOPLE: International Journal of Social Sciences, 2017)
The contemporary entrepreneurship of Russia is being formed in the course of move towards market relations for over thirty years in rapidly changing conditions of the national market emergence. The latest decade alone enables to specify two stages in the development of the Russian entrepreneurship while the receding twenty years saw three of them. For such sharp changes of the entrepreneurship environment this situation looks like a crisis, however a few researchers opine that under the foreign economic pressure of the Russian economy the entrepreneurship community may, upon strengthening its position, get an impulse for further development. This historical research show us how were the entrepreneurships training influence for theirs activity in the Far Eastern subjects of Russia.